The Pricing of Durable Exhaustible Resources - Levhari, David; Pindyck, Robert S. (Quarterly Journal of Economics, 1981)
Partial or total durability characterizes a large class of exhaustible resources. We show that Hotelling's r-percent rule will apply to a durable resource produced in a competitive market, but will not apply if the resource is produced in a monopolistic market. However, the r-percent rule does not mean that price is steadily rising. We show that in general the competitive market price will fall initially as the stock in circulation increases, and later will rise as the stock decreases and eventually depreciates toward zero after production ceases. Accounting for durability may thus help explain the U-shaped long-term price profiles observed for many resources.